Evaluation of coating resistivity for pigmented/unpigmented epoxy coatings under marine alternating hydrostatic pressure. (20th February 2021) - Meng, Fandi; Liu, Li; Cui, Yu; Wang, Fuhui
Abstract: To realize a rapid evaluation of coating degradation under alternating hydrostatic pressure (AHP), appropriate physical models of electrochemical impedance spectroscopy (EIS) data fitting were respectively developed for epoxy coatings with and without pigments, based on their different water absorption behaviours. Power-law model was selected to evaluate the anti-permeability of epoxy varnish (EV) coating, which tends to form through pores in the coating structure. On the other hand, two-layer model based on Young theory was developed to evaluate the anti-permeability of pigmented epoxy coating. Consequently, the resistivity profile with coating thickness was calculated as a critical parameter to describe the anti-permeability of coating at different immersion time. The interpretation of water diffusion dynamics based on different coating structures was also given, which is responsible for the choice of distribution models.